Description and Phylogenetic Studies on the Complete Mitochondrial Genome of Kingdonella qinghaiensis Zheng (Insecta: Orthoptera: Acrididae) - Liu, Xiaoli; Fu, Yun; Li, Xinxin; Li, Yuan; Liu, Jizhuang; Hu, Yang; Xueting, Hong; Ding, Xunhuan; Sun, Tao (Zootaxa, 2025)
Kingdonella qinghaiensis Zheng, 1990 a species belonging to the genus Kingdonella Uvarov, 1933, within the family Acrididae in the order Orthoptera, is mainly distributed in Qinghai province, China. In this study, we determined, assembled and annotated the mitochondrial genome of Kingdonella qinghaiensis. The mitogenome is 15,597 bp in length and contains 13 protein-coding genes (PCGs), 22 tRNA genes, 2 rRNA genes and a control region (D-loop). The entire mitogenome exhibits a strong A/T bias, with an A+T content of 75.4%. All 13 PCGs had the typical start codon of ATN (9 ATGs, 2 ATCs and 2 ATTs) and TAA was the most frequent stop codon in Kingdonella qinghaiensis PCGs, except TAGs for ND3 and ND1 genes. A total of 3,730 codons are present in the mitogenomic PCGs of Kingdonella qinghaiensis. Among these, UUA (9.65%) is the most frequent codon for leucine (L), followed by AUU (9.3%) for isoleucine (I), and UUU (8.12%) for phenylalanine (F). The Ka/Ks ratios of the 13 PCGs in Kingdonella qinghaiensis mitogenome ranged from 0.1436 to 0.9107 (0<Ka/Ks<1), and ND4L had the highest ratio while COX1 gene had the lowest value. The nucleotides diversity (Pi) analysis of the 13 PCGs from 46 species in Acrididae implied that ND2 gene contained the highest variability site (0.27862). While ND5, ND4 and ND1 had comparatively low nucleotide diversities. The phylogenetic tree based on the nucleotide sequences of the 13 PCGs from 46 different species (including 2 outgroups) supported the monophyly of Acrididae and indicated two stable clades in Acrididae. The phylogenetic analyses represented the main topology as follows: ((((Catantopinae+Calliptaminae) +Cyrtacanthacridinae) + ((Spathosterninae+Oxyinae) + Melanoplinae)) + (((Oedipodinae+Acridinae) + Gomphocerinae) +Coptacrinae)). Species from Melanoplinae in the phylogenetic tree confirmed that Kingdonella qinghaiensis had the closer taxonomy relationship with Kingdonella bicollina, another member in the same genus.